Small represents the great - Cheng, Guihua (Hong Kong Tang Art Design & Information Group Ltd., 2012)
The rapid development of real estate boosts the landscape industry, which is developing at an unprecedented speed and has been recognized by more and more as the key factor that determines the quality of property. Thus, books on landscape draw increasing attention from landscape designers and fans.
Keywords: HAWKINSRESIDENCE; LACASAATENCANTERRA; LANDSCAPE ARCHITECTURE (AR-LA)